(untitled) (Olhar de Professor, 2022)
This article seeks to reflect on the possibility of the educational process in the prison system to act in changing the living conditions of individuals in situation of deprivation of freedom, from humanized and liberating methodological practices adopted by teachers of these spaces. As a result, it is intended to identify, in these environments, the existence of didactic-pedagogical actions and resources that aim to ensure that young prisoners have access to education. The analysis is based on a literature review of bibliographic and documental nature, as a support to the reflections about how the educational process for people in situation of freedom deprivation is nowadays, seeking to highlight education as a tool capable of promoting the (re)construction of citizenship and the reinsertion of these individuals to social life.